2022
DOI: 10.1097/brs.0000000000004333
|View full text |Cite
|
Sign up to set email alerts
|

ALIF Versus TLIF for L5-S1 Isthmic Spondylolisthesis: ALIF Demonstrates Superior Segmental and Regional Radiographic Outcomes and Clinical Improvements Across More Patient-reported Outcome Measures Domains

Abstract: L5-S1 isthmic spondylolisthesis is a common pathology that can lead to operative intervention; as appreciation of sagittal balance has evolved, interbody fusions have gained popularity. Our study demonstrates the radiographic and clinical superiority of ALIFs over TLIFs in the form of PROMs at short-term and greater than one year follow up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 29 publications
(64 reference statements)
1
10
1
Order By: Relevance
“…13 A separate study by Kim et al 12 Previous literature has illustrated that ALIF demonstrates superior segmental and regional lordosis correction compared with TLIF. [23][24][25] Greater lordotic correction may allow for decreased rates of adjacent segment degeneration among TLIF patients, as reported by Lee et al 26 Of note, our PROM scores and MCID achievement rates were equal in the past 12 weeks, suggesting that improvements in lordosis from ALIF may not necessarily implicate superior improvements in quality-of-life outcomes. This concept is closely related to statements by Horsting et al, 27 which note that radiographic adjacent segment disease may not influence clinical outcome scores.…”
Section: Discussionsupporting
confidence: 66%
“…13 A separate study by Kim et al 12 Previous literature has illustrated that ALIF demonstrates superior segmental and regional lordosis correction compared with TLIF. [23][24][25] Greater lordotic correction may allow for decreased rates of adjacent segment degeneration among TLIF patients, as reported by Lee et al 26 Of note, our PROM scores and MCID achievement rates were equal in the past 12 weeks, suggesting that improvements in lordosis from ALIF may not necessarily implicate superior improvements in quality-of-life outcomes. This concept is closely related to statements by Horsting et al, 27 which note that radiographic adjacent segment disease may not influence clinical outcome scores.…”
Section: Discussionsupporting
confidence: 66%
“…Previous studies have found a greater generation of segmental lordosis and disc height for ALIF procedures compared to TLIF procedures, however, the biomechanical benefit associated with ALIF does not necessarily translate to improvement in PROs 29,30. In fact, our findings suggest that ID may even be associated with worse short-term pain evidenced by less improvement of leg pain and back pain in the early postoperative period at 3 months.…”
Section: Discussioncontrasting
confidence: 57%
“…Previous studies have found a greater generation of segmental lordosis and disc height for ALIF procedures compared to TLIF procedures, however, the biomechanical benefit associated with ALIF does not necessarily translate to improvement in PROs. 29,30 In fact, our findings suggest that ID may even be associated with worse short-term pain evidenced by less improvement of leg pain and back pain in the early postoperative period at 3 months. Whether this was due to residual leg pain from inadequate decompression or thigh pain from the transpsoas approach is unclear, and overall, the differences normalized at 12 months and both groups achieved good outcomes.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Aggregating the multitude of data and deciding on a specific procedural plan is rather complex and often a group of spine surgeons will arrive at differing solutions to a similar clinical presentation. 24,25 While there may be any number of acceptable procedural solutions for a given patient with a specific pathology which will result in clinical improvement, there is likely a single optimal or ideal solution. In the future, with broader availability of data around patient clinical and anatomic factors, as well as outcome data, it is likely that spine physicians will have access to data-driven decision aids integrated into electronic health platforms.…”
Section: Data and Decision Aidsmentioning
confidence: 99%